The influence of anastomotic leakage on patients’ outcomes after rectal cancer surgery - Kim, Young Wan; Kim, Bo Ra (Annals of Laparoscopic and Endoscopic Surgery, 2017)
Rectal cancer surgery is still evolving and various resection techniques such as laparoscopy, robotics, or transanal minimally invasive surgery have been introduced (1).